3D printing throws a wrench in the works for the Craftsman brand - Allen, Charlotte, active 2019; Harden, Gina; Fisher, Warren W. (London : SAGE Publications: SAGE Business Cases Originals, 2019)
Frances, a marketing consultant, was contacted by a former colleague, Rupert, who is now the brand manager for Craftsman tools. Rupert is concerned about a video depicting the apparent 3D printing of a Craftsman wrench. The case deals with the current and future impact of 3D printing and social media on branding, business strategy, and distribution. Students are put in the situation of a marketing consultant who must determine what advice to impart to the Craftsman brand manager as he navigates the impacts of emerging technologies.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Stanley Black & Decker Inc; Product management -- Study and teaching -- Activity programs; Product management -- Case studies; Three-dimensional printing -- Economic aspects -- Case studies